A low-passage insect-cell isolate of bluetongue virus uses a macropinocytosis-like entry pathway to infect natural target cells derived from the bovine host. (7th March 2019) - Stevens, Lisa M.; Moffat, Katy; Cooke, Lyndsay; Nomikou, Kyriaki; Mertens, Peter P. C.; Jackson, Terry; Darpel, Karin E.
Abstract : Bluetongue virus (BTV) causes an economically important disease in domestic and wildlife ruminants and is transmitted by Culicoides biting midges. In ruminants, BTV has a wide cell tropism that includes endothelial cells of vascular and lymphatic vessels as important cell targets for virus replication, and several cell types of the immune system including monocytes, macrophages and dendritic cells. Thus, cell-entry represents a particular challenge for BTV as it infects many different cell types in widely diverse vertebrate and invertebrate hosts. Improved understanding of BTV cell-entry could lead to novel antiviral approaches that can block virus transmission from cell to cell between its invertebrate and vertebrate hosts. Here, we have investigated BTV cell-entry using endothelial cells derived from the natural bovine host (BFA cells) and purified whole virus particles of a low-passage, insect-cell isolate of a virulent strain of BTV-1. Our results show that the main entry pathway for infection of BFA cells is dependent on actin and dynamin, and shares certain characteristics with macropinocytosis. The ability to use a macropinocytosis-like entry route could explain the diverse cell tropism of BTV and contribute to the efficiency of transmission between vertebrate and invertebrate hosts.